Fatores de influência no processo de retenção discente: um estudo com alunos de graduação em Ciências Contábeis em uma IES de iniciativa privada - Braga, Luis Felipe Hortenzi Vilela (2016)
This dissertation has two main objectives, the first to identify parameters to assess the efficiency and effectiveness of undergraduate education in Accounting and the second generating useful information for strategic planning of the education system, the IES, and of Accounting Courses, by means of student retention factors proposed by Cabrera, Nora and Castanheda (1992).The methodological approach applied descriptive and inferential statistics continuing the Exploratory Factor Analysis, Confirmatory Factor Analysis and finalizing this study with the proposition of a model compound for Structural Equation. The results confirm using the covariance matrix of the structural equation modeling showed that 7 between 12 causal relationships respectively comparing with the model of Cabrera et al. (1992 ). Among the exogenous variables as well as in the reference model the encouragement of close people got more weight in the model of explanation, from a causal relationship 0.885 with academic and intellectual development, and 0.714 from social integration; between endogenous variables academic and intellectual development was the most important factor with a causal relationship 0.720 with commitment to the institution and 0.432 in order to graduating. It was concluded by the results that the adaptation of the model proposed by Cabrera, Nora and Castaneda (1992) and its implementation, were able to identify parameter for management of Accounting courses and contribute to future research, expanding discussions on education, management and vocational training in Accounting